2020
DOI: 10.1177/1550059420933142
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Beta Activity in the Meta-Intention of Children With Attention Deficit Hyperactivity Disorder

Abstract: Children with attention deficit hyperactivity disorder (ADHD) have high theta and low beta activity in the frontal lobe. The higher the theta/beta ratio, the lower the level of central nervous system (CNS) cortical arousal. However, there is seldom evidence between electroencephalograms (EEGs) and the patient’s intentionality to regulate the cortical activity of executive attention tasks. We investigated whether children with ADHD intended to improve their performance in executive attention tasks and whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…5,19 Several studies have also reported no significant differences in TBR between healthy and ADHD people. 5,20,21 There are even several investigations reporting higher TBR in healthy cases compared with those affected with ADHD. 6,10,[22][23][24][25][26] This result indicates that TBR has grown rapidly in healthy people in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…5,19 Several studies have also reported no significant differences in TBR between healthy and ADHD people. 5,20,21 There are even several investigations reporting higher TBR in healthy cases compared with those affected with ADHD. 6,10,[22][23][24][25][26] This result indicates that TBR has grown rapidly in healthy people in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However,the EXP maintained their mental effort when dealing with attention tasks at the post-test, while the CON did not. 19 The results still show the feasibility of this training location. 56 (2)At the neurophysiological and neuropsychological level,Thompson & Thompson 57 and Fuchs et al 58 pointed out that neurofeedback can improve distracted and impulsive indicators of multi-dimensional attention tests to increase processing speed and reduce instability, that increased the accuracy rate of multilevel attention abilities and improved EF related to the prefrontal lobe.…”
Section: Discussionmentioning
confidence: 79%
“…The CON showed more TBR while doing the tasks, which might mean that the CON could not maintain the cortical arousal in the post-test. 7,13,19 The neuropsychological level results showed that WWNF could enhance sensory selection and attention control accuracy in the Go/No-Go subtests, increase cognitive flexibility by decreasing preservation errors, and increase concept formation and planning abilities. From the parents’ view of behavioral symptoms and functions, WWNF training reduced ADHD symptoms, especially the large effect of inattention symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the neurofunctional level, the role of the left premotor cortex has been described in the ability for conscious correction of an error with both hands [24]. Finally, there have been several case reports at the level of stimulation in favor of error correction, including the greater implication of auditory sensory information over visual information when an individual must correct an error [25] and the importance of visual feedback in the error correction ability [26][27][28].…”
mentioning
confidence: 99%